Essential Biodiversity Variables for measuring change in global freshwater biodiversity. (September 2017) - Turak, Eren; Harrison, Ian; Dudgeon, David; Abell, Robin; Bush, Alex; Darwall, William; Finlayson, C. Max; Ferrier, Simon; Freyhof, Jörg; Hermoso, Virgilio; Juffe-Bignoli, Diego; Linke, Simon; et al.
Abstract: A critical requirement in assessing progress towards global biodiversity targets is improving our capacity to measure changes in biodiversity. Global biodiversity declined between 2000 and 2010, and there are indications that the decline was greater in freshwater than in terrestrial or marine systems. However, the data, tools and methods available during that decade were inadequate to reliably quantify this decline. Recent advances in freshwater monitoring make a global assessment now close to becoming feasible. Here we identify priorities for freshwater biodiversity assessment for 2020 and 2030, based on the Essential Biodiversity Variables (EBV) framework. We identify 22 priority activities for 2020 under three of the EBV classes (species populations, community composition, and ecosystem structure), which include: a globally systematic approach to collecting and assessing species data, collating existing and new data within global platforms, coordinated effort towards mapping wetland extent at high spatial resolution, linking in-situ data to modelling across regions, and mobilising citizen science for the collection and verification of data. Accomplishing these will allow the state of global biodiversity to be assessed according to a Red List Index with expanded geographic and taxonomic cover, an improved freshwater Living Planet Index with a greater number and phylogenetic range of species, measures of alpha and beta diversity, and globally-consistent estimates of wetland extent. To assess variables in the other EBV classes (genetic composition, species traits, and ecosystem function) we identify 15 priorities, which include development of environmental DNA methods, species-traits databases, eco-informatics and modelling over the next 15 years. Highlights: Essential Biodiversity Variables (EBV) streamlines biodiversity monitoring. EBVs can help tracking change in global freshwater biodiversity. Using EBVs we identified 22 priority actions for 2020 and 15 for 2030. 2020 priorities: species populations; community composition; ecosystem structure 2030 priorities: genetic composition; species traits; and ecosystem function